Assessment of current clinical practices for major depression in Japan using a web-based questionnaire - Hori H (Dove Medical Press, 2019)
Hikaru Hori,1 Kentaro Yamato2 1Department of Psychiatry, University of Occupational and Environmental Health, Kitakyushu, Fukuoka, Japan; 2JPBU Department of Medical Affairs, Takeda Pharmaceutical Co. Ltd., Tokyo, JapanCorrespondence: Kentaro YamatoJPBU Department of Medical Affairs, Takeda Pharmaceutical Co. Ltd., 1-1 Nihonbashi-honcho 2-chome, Chuo-ku, Tokyo 103-8668, JapanTel +81 33 278 3244Fax +81 33 278 2925Email kentarou.yamato@takeda.comPurpose: To investigate the current clinical practice of Japanese physicians in the diagnosis and management of major depression (major depressive disorder [MDD]).Patients and methods: Japanese physicians specializing in psychiatry or psychosomatic medicine in the medical database of Nihon Ultmarc Inc. (Chuo-Ku, Tokyo, Japan), who had treated ≥30 patients with MDD in the past month were invited to complete a web-based questionnaire from January 15 to 29, 2018. The questionnaire was comprised of 28 questions pertaining to the physician’s background, the criteria and tools used to diagnose MDD during physician–patient consultation, and actual and preferred duration of physician–patient consultation. Responses were given as single answer numerical values or as multiple-choice answers.Results: From the 518 physicians invited to participate, 340 completed questionnaires were analyzed. Respondents were predominantly male (90%), hospital based (73%), affiliated with the Department of Psychiatry (95%), and members of the Japanese Society of Psychiatry and Neurology (87%). The majority of physicians (84%) agreed that “improvement of cognitive dysfunction caused by major depression is an important factor for patients to return to work” was the most challenging aspect of MDD diagnosis and management. Moreover, 83% of physicians conducted psychological assessments using a cognition evaluation test with most of their patients at the time of MDD diagnosis; the most commonly used tool was the Hasegawa Dementia Scale-Revised. Both hospital-based physicians and general practitioners would prefer to have longer consultations with their patients.Conclusion: Physicians acknowledge the importance of the assessment and management of cognitive dysfunction in patients with MDD. However, most physicians would prefer to have longer consultation times with their patients for the diagnosis of MDD. In the future, it may be useful to introduce digital tools (eg, THINC-it®) for the initial screening of cognitive dysfunction.Keywords: Japan, survey, diagnosis, management, major depression disorder